Impact of Continuous Kidney Replacement Therapy and Hemoadsorption with CytoSorb on Antimicrobial Drug Removal in Critically Ill Children with Septic Shock: A Single-Center Prospective Study on a Pediatric Cohort - Gabriella Bottari; Bianca Maria Goffredo; Marco Marano; Cristina Maccarrone; Raffaele Simeoli; Giuseppe Bianco; Leonardo Vallesi; Joseph Charles Charlie Beetham; Anna Teresa Mazzeo; Andrea Cappoli; Sara Cairoli; Raffaella Labbadia; et al. (MDPI AG, 2023)
Background: Extracorporeal therapies (ET) are increasingly used in pediatric settings as adjuvant therapeutic strategies for overwhelming inflammatory conditions. Although these treatments seem to be effective for removing inflammatory mediators, their influence on antimicrobials pharmacokinetic should not be neglected. Methods: A prospective observational study of children admitted to the pediatric intensive care unit (PICU) with a diagnosis of sepsis/septic shock. All critically ill children received hemoadsorption treatment with CytoSorb (CS) in combination with CKRT. Therapeutic drug monitoring has been performed on 10 critically ill children, testing four antimicrobial molecules: meropenem, ceftazidime, amikacin and levofloxacin. In order to evaluate the total and isolated CKRT and CS contributions to antibiotic removal, blood samples at each circuit point (post-hemofilter, post-CS and in the effluent line) were performed. Therefore, the clearance and mass Removal (MR) of the hemofilter and CS were calculated. Results: Our preliminary report describes a different impact of CS on these target drugs removal: CS clearance was low for amikacine (6-12%), moderate for ceftazidime (43%) and moderate to high for levofloxacine (52-72%). Higher MR and clearance were observed with CKRT compared to CS. To the best of our knowledge, this is the first report regarding pharmacokinetic dynamics in critically ill children treated with CKRT and CS for septic shock.